Trends in Household Coverage of Modern Infrastructure Services in Africa - (:unkn) unknown (My University, 2009)
Household surveys have long been used to estimate poverty and inequality trends, as well as trends in education and health indicators, but they have not been used to the same extent to assess trends in the access to or coverage of modern infrastructure services. In this paper, we use Demographic and Health Surveys from a larger sample of sub-Saharan African countries in order to collect comparable information across countries on coverage of piped water, flush toilets, electricity, and landline telephones over time. The results suggest that coverage rates for electricity, flush toilets have improved slightly over the last decade. Coverage of piped water has declined, at the same time as coverage of landline (as well as cellular) telephone has increased rapidly. The decline has been primarily in the urban areas while the infrastructure coverage has either increased or remained stable in rural Africa. For all four services, among the poorest households coverage remains virtually inexistent. If business as usual continues, it would take a very long time to reach universal or widely shared coverage even in countries where coverage has improved. These results point to the need to increase efforts by governments and international community to progressively increase access to modern infrastructure services in Africa.
Keywords: African Research